The Effect of Liquidity Risk, Credit Risk, Operational Risk, Market Risk and Good Corporate Governance on Financial Performance in Conventional Commercial Banks Listed on The Indonesia Stock Exchange - Reydeska Natalia A A Gulo; Noni Ardian; Ramadhan Harahap (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of liquidity risk, credit risk, operational risk, market risk, and Good Corporate Governance on the financial performance of conventional commercial banks listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This study uses a quantitative method with a panel data regression approach. The research population is all conventional commercial banks listed on the Indonesia Stock Exchange, with a sample of 41 banks that meet the purposive sampling criteria for the 2022-2024 period, resulting in 123 observations. Data analysis was carried out using EViews 12 software. The results of the study show that simultaneously liquidity risk, credit risk, operational risk, market risk, and Good Corporate Governance have a significant effect on the financial performance of conventional commercial banks. Partially, credit risk and operational risk have a negative and significant effect on financial performance, while market risk and Good Corporate Governance have a positive and significant effect on financial performance. Meanwhile, liquidity risk does not have a significant effect on financial performance. The Adjusted R-squared value of 0.607560 indicates that 60.76% of the variation in financial performance (ROA) can be explained by liquidity risk variables, credit risk, operational risk, market risk, and Good Corporate Governance, while the remaining 39.24% is influenced by other variables outside the research model.